2009
DOI: 10.1021/op9000675
|View full text |Cite
|
Sign up to set email alerts
|

Kilogram-Scale Synthesis of the CXCR4 Antagonist GSK812397

Abstract: An improved, scalable synthesis of the CXCR4 antagonist GSK812397 is described. This new route was recently scaled up in 50 L fixed equipment to afford 1.2 kg of drug substance in five steps with an overall yield of 20% and >99% chemical and enantiomeric purity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…2). This hypothesis agrees with the assumptions M a n u s c r i p t 15 proposed by Srivastava et al 74 and Garcia-Perez et al 75 We considered that the best AMD11070 and GSK812397 poses found ( Figure 5) should represent better CXCR4-ligand interactions. Indeed, if we analyze these best docked structures we find how they fill the central region of subsite 1-2 ( Figure 9).…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…2). This hypothesis agrees with the assumptions M a n u s c r i p t 15 proposed by Srivastava et al 74 and Garcia-Perez et al 75 We considered that the best AMD11070 and GSK812397 poses found ( Figure 5) should represent better CXCR4-ligand interactions. Indeed, if we analyze these best docked structures we find how they fill the central region of subsite 1-2 ( Figure 9).…”
Section: Figuresupporting
confidence: 91%
“…Similarly, Boggs et al 15 synthetized the small organic compound GSK812397 (Figure 1), a bioavailable and oral noncompetitive antagonist of CXCR4, which inhibits HIV entry. This pharmacological compound has a high selectivity and may be able to bind CXCR4 in a distinct and separate site than HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some commercially available drugs contain this core structure (Figure 1), such as A (Zolimidin; to treat pepticulcer), 19 B (minodronic acid; to treat osteoporosis), 20 C (Alpidem; a peripheral benzodiazepine receptor ligand), 21 D (GSK812397; a potent noncompetitive CXCR4 receptor antagonist). 22 Consequently, extensive efforts have been devoted to the discovery of efficient and useful methods for imidazoheterocycle synthesis and functionalization. 23 Besides that, to explore new methods for C-3 functionalization of imidazopyridines has made significant progress, but unfortunately examples remain rather limited.…”
Section: Figure 1 Representative Examples Of C-3 Substituted Imidazomentioning
confidence: 99%
“…3), such as alpidem 1.1 (anxiolytic) [8], zolpidem 1.2 (hypnotic, to treat insomnia) [9], necopidem 1.3 [10], saripidem 1.4 (sedative and anxiolytic), zolimidine 1.5 (anti-ulcer, used for treatment peptic ulcer) [11], olprinone 1.6 (to treat acute heart failure) [12] and minodronic acid 1.7 (to treat anxiety, heart failure, osteoporosis) [13]. This basic structure also exists in GSK812397 1.8 (HIV infection) [14], PI3Ka inhibitors 1.9, mGlu2 receptors 1.10 [15], TNF-a inhibitors 1.11 [16] and insecticide activity against pea aphids 1.12 [17] Furthermore, this basic core moiety is obtained in many pharmaceutical compounds (Fig. 4) that display benzodiazepine receptor agonist [18], calcium channel [19], antifungal [20], antitumor [21], antiviral [22], antibacterial, analgesic [23] and anti-HIV properties [24].…”
Section: Introductionmentioning
confidence: 99%